INFLUENCE OF THE QUALITY OF ELECTRONIC SERVICES (WEBSITE DESIGN, CUSTOMER SERVICE, SECURITY/PRIVACY, FULFILMENT) ON CUSTOMER SATISFACTION AND REPURCHASE INTEREST IN THE McDONALD'S APPLICATION - Dhiya Athaya Gusfi; Saputri, Marheni Eka (Fakultas Seni Rupa dan Desain ITB, 2024)
With the rapid advancement of technology, many companies are innovating online sales to increase consumer convenience when ordering food. Nowadays, competition among companies is getting fiercer, urging businesses to continuously improve their service quality to attract customers' interest in making repeat purchases. The purpose of this study is to investigate how customer satisfaction and repurchase interest in the McDonald's app are affected by e-service quality, which includes issues such as website design, customer service, security/privacy, and fulfillment. The study population wasMcDonald's app users in Bandung City, with 400 respondents taken through online questionnaire distribution through social media. The method used SEM-PLS for data analysis, and the sampling procedure was conducted with purposive sampling. The findings show that website design positively and significantly affects e-service quality, customer service positively and significantly affects e-service quality, security/privacy positively and significantly affects e-service quality, and fulfillment positively and significantly affects e-service quality, e-service quality positively and significantly affects customer satisfaction, and customer satisfaction positively and significantly affects repurchase intention on the McDonald's app.